Effect of secondary emission on the afterglow of argon with negatively charged dust particles - Denysenko, I.B.; Stefanović, I.; Azarenkov, N.A.; Burmaka, G.P. (Вопросы атомной науки и техники, 2014)
A theoretical model for an argon/dusty plasma afterglow in presence of nano-sized dust particles with large density is developed. According to the model, in the plasma afterglow the electrons are generated in metastable collisions and in the secondary emission by collisions of ions with electrodes. By using the model and experimental time-dependencies for metastable density and electrode bias, the time-dependencies for electron density in argon/dusty plasma afterglow are calculated. The effect of secondary emission on electron generation in argon/dusty plasma afterglow is analyzed.